2017
DOI: 10.3892/ol.2017.7152
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of anti‑sperm‑associated antigen 9 antibody are elevated in patients with hepatocellular carcinoma

Abstract: Abstract. At present, there is a high incidence of viral hepatitis and high mortality rates due to hepatocellular carcinoma (HCC) in China. In the current study, the quantification of antibodies against the cancer-testis antigen sperm-associated antigen 9 (SPAG9), alone and combined with α-fetoprotein (AFP), were evaluated as biomarkers for the diagnosis of HCC. The levels of anti-SPAG9 antibody and AFP were quantified in serum samples from patients with HCC and hepatitis or cirrhosis, as well as healthy vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…For instance, the levels of anti-sperm-associated antigen 9 (SPAG9) antibodies were significantly higher compared with those in patients with hepatitis/cirrhosis or healthy controls. When combined with anti-SPAG9 antibodies and α-fetoprotein (AFP) levels, the diagnostic specificity and sensitivity were further improved [ 55 ].…”
Section: Cancer Auto-antibodiesmentioning
confidence: 99%
“…For instance, the levels of anti-sperm-associated antigen 9 (SPAG9) antibodies were significantly higher compared with those in patients with hepatitis/cirrhosis or healthy controls. When combined with anti-SPAG9 antibodies and α-fetoprotein (AFP) levels, the diagnostic specificity and sensitivity were further improved [ 55 ].…”
Section: Cancer Auto-antibodiesmentioning
confidence: 99%
“…Early diagnosis of HCC offers patients a better chance for long-term survival[ 5 ]. Although imaging technologies such as magnetic resonance imaging and ultrasonography, and serum biomarkers [notably α-fetoprotein (AFP)] are widely used to diagnose HCC in the clinic[ 6 ], they are far from satisfactory because they lack sensitivity and specificity[ 7 ]. Therefore, there is an urgent and unmet desire for novel screening methods and new biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, sperm associated antigen 9 (SPAG9) has been shown to be expressed in various cancer types such as epithelial ovarian cancer (EOC-90%) [13], renal cell carcinoma (RCC-88%) [14], colorectal cancer (74%) [15], breast cancer (88%) [16] and cervical cancer (82%) [17]. Studies on SPAG9 also showed that it is associated with cellular proliferation, migration and invasion of cancer cells [18][19][20][21], and is capable of eliciting humoral immune responses in a majority of epithelial ovarian cancers (67%) [13], breast cancers (80%) [16], cervical cancers (80%) [17], renal cell carcinoma (77%) [14], colorectal cancer (74%) [15] and hepatocellular carcinoma [22]. However its antigenicity in invoking a cell mediated immune response has not been studied until now.…”
Section: Introductionmentioning
confidence: 99%